Perinatal Palliative Care Birth Planning as Advance Care Planning - Cortezzo, DonnaMaria E.; Ellis, Kelstan; Schlegel, Amy (Frontiers in Pediatrics, 2020)
Purpose of review A significant number of pregnancies are complicated by a fetus with a life-limiting diagnoses. As diagnoses are made earlier in the pregnancy, families experience anticipatory grief and are faced with navigating goals of care for a baby that has yet to be born. With the support of the care team, families can begin to grieve, plan, and make meaningful memories both during the duration of the pregnancy and for the potentially short life of the child. Birth planning has become an important method for parents to process the diagnoses, for parents to document their wishes, and for members of the care team to communicate with the goal of supporting and enhancing the experience of the family. This articles reviews recent and relevant literature on the importance of birth planning and the role of perinatal palliative care when a life-limiting fetal diagnosis is made. Recent findings The process of birth planning is an important component of perinatal palliative care. Through this process, families can express their fears, values, hopes, and wishes. It also offers an opportunity for providers to communicate are wishes for the remainder of the pregnancy, the delivery, birth, and time afterwards. This has been demonstrated to decrease maternal stress and promote family centered care. Summary Perinatal birth planning is an important component of perinatal palliative care when a fetus has a life-limiting diagnosis. The process of birth planning can be supportive and therapeutic as well as an important communication tool. With multiple practices and designs of perinatal palliative care programs, there are no standard tools even though important components have been identified. Ultimately, the strategies outlined here can be used as advance care planning tools.